Energy Savings for Air Conditioning System Using Fuzzy Logic Controller Design for Northeastern Nigeria - Maxwell Francis; Raji Luqman; Dadiyo Charles; Anjili Audu (Bandung State Polytechnic (Politeknik Negeri Bandung), 2022)
Efficient air cooling in an air conditioning system minimizes power consumption. The air conditioning system is considered one of the home appliances in which a massive amount of electrical energy is recorded, especially in the urban area. In this work, the fuzzy logic controller is designed to save energy for northeastern Nigeria using six and two input and output parameters respectively. The input parameters consist of the temperature of the user, temperature difference, number of occupants, time of the day, dew point temperature, and weather conditions. The output parameters consist of compressor speed and operation mode. The controller performance was simulated. The controller is designed in such a way that it can control the compressor speed leading to energy savings, and the operation mode to optimize humidity conditions, and when the room gets hot, it switches to air conditioning. The simulated result showed that a good percentage of electrical power could be saved when fuzzy logic is utilized